2021
DOI: 10.3390/jof7030181
|View full text |Cite
|
Sign up to set email alerts
|

Three New Derivatives of Zopfinol from Pseudorhypophila Mangenotii gen. et comb. nov.

Abstract: Triangularia mangenotti was analyzed for the production of secondary metabolites, resulting in the isolation of known zopfinol (1) and its new derivatives zopfinol B–C (2–4), the 10-membered lactones 7-O-acetylmultiplolide A (5) and 8-O-acetylmultiplolide A (6), together with sordarin (7), sordarin B (8), and hypoxysordarin (9). The absolute configuration of 1 was elucidated by the synthesis of MPTA-esters. Compound 1 showed antimicrobial activity against the Gram-positive bacteria Bacillus subtilis and Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Moreover, the new genus Pseudorhypophila was introduced based on the production of the same class of compounds, i.e. zopfinol and derivatives, by members of the same monophyletic lineage (Harms et al 2021). In this later work, they observed that producers of sordarins, which are a class of natural antifungal agents, were all located in the Naviculisporaceae, supporting the introduction of this family based on molecular data by Marin-Felix et al (2020).…”
Section: Conclusion and Final Remarksmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the new genus Pseudorhypophila was introduced based on the production of the same class of compounds, i.e. zopfinol and derivatives, by members of the same monophyletic lineage (Harms et al 2021). In this later work, they observed that producers of sordarins, which are a class of natural antifungal agents, were all located in the Naviculisporaceae, supporting the introduction of this family based on molecular data by Marin-Felix et al (2020).…”
Section: Conclusion and Final Remarksmentioning
confidence: 82%
“…No sequences in Chaetomiaceae were included since no novelties were proposed in this family (Table 2). The maximum likelihood (ML) and Bayesian inference (BI) analyses including the four loci were performed as described by Harms et al (2021). The lengths of the individual alignments used in the combined dataset were 556 bp (ITS), 916 bp (LSU), 978 bp (RPB2) and 618 bp (TUB2), and the final combined alignment was 3068 bp.…”
Section: Introductionmentioning
confidence: 99%
“…The fungal species Triangularia mangenotii belongs to be the phylum Ascomycota . It has been reported that the relative abundance of Triangularia mangenotii decreased in heavy metal Pb–Zn contaminated soil ( Harms et al, 2021 ). However, Triangularia mangenotii and Ciliophora sp .…”
Section: Discussionmentioning
confidence: 99%
“…Individual gene phylogenies were verified for conflicts before the three locus datasets were concatenated 47 , 48 . The maximum-likelihood (ML) and Bayesian inference analyses including the three loci were performed as described by Harms et al 49 . The best evolutionary model for each sequence dataset was calculated with MrModeltest v. 2.3 50 .…”
Section: Methodsmentioning
confidence: 99%